From subjects to objects: Knowledge in International Relations theory - Allan, Bentley B. (European journal of international relations, 2018)
There has been a resurgence of interest in the role of scientific knowledge and expertise in International Relations, but it is not clear what the theoretical value-added of this work is. This article places recent work on scientific knowledge and expertise in a longer-term perspective. The history shows that knowledge has played an important role in International Relations theory since Carr and Morgenthau, but that thinking has been trapped within a simple conceptual framework centered on tracing how knowledge shapes the beliefs and interests of international subjects. This mode of theorizing first entered International Relations via Mannheim and has been further developed by Foucauldian and practice-based approaches since the 1990s. Outlining the history of knowledge from Carr through Haas to the present makes it possible to identify the distinctive contribution of recent work: whereas International Relations has focused on how knowledge shapes subjects such as states and international organizations, recent work by Corry, Sending, and others reorients International Relations to the constitution of governance objects. On the object-centered view, knowledge plays a key role in the construction of the hybrid entities like the economy and the climate that structure the landscape of international politics.